Generalfeldmarschall Göring on his 46th birthday. He receives "Baumkuchen und Gebäck" from the "Reichsstelle des deutschen Handwerks in der deutschen Arbeitsfront". Text on the back
Generalfeldmarschall Göring on his 46th birthday. He receives "Baumkuchen und Gebäck" from the "Reichsstelle des deutschen Handwerks in der deutschen Arbeitsfront". Text on the back.